Female Student Prevention on Health Awareness at Padjadjaran Vocational High School - Rifiza, Muhammad Irfa; Dermawan, Windy; Nurhayati, Heni (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2024)
Healthy generation is one of the keys to achive